The role of DOF transcription factors in generating specificity during plant development - Hidalgo, Inés; Lohmann, Jan U. (The journal of experimental botany, 2026)
DNA binding with one zinc finger (DOF) transcription factors (TFs) are specific to plants and have been shown to play diverse roles in plant-specific processes. However, their involvement in plant development is often obscured due to genetic redundancy. In this review, we focus on recent discoveries on the function of DOF TFs during plant development. We highlight the interplay between phytohormones, specifically auxin and cytokinin, and DOF TFs in the regulation of cambium proliferation, phloem development, and flower formation. We also discuss described roles of DOF TFs in plant regeneration. In the second part of the review, we examine reported interaction between DOF TFs and other proteins and transcriptional regulators. We emphasize the interactions between CYCLING DOF FACTORS (CDFs) and other proteins, which are necessary for a proper control of flowering time. Moreover, we highlight the interaction between the TFs CDF2 and PHYTOCHROME-INTERACTING FACTOR 4 (PIF4) as an example of how the joint activity of two different TFs can enhance the association to DNA and to the cooperative regulation of target genes. Lastly, we discuss challenges and future directions in the study of DOF TFs.